2017
DOI: 10.1016/j.bbi.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Increased inflammation from childhood to adolescence predicts sleep apnea in boys: A preliminary study

Abstract: While chronic systemic inflammation in obstructive sleep apnea (OSA) has been traditionally considered a consequence of intermittent hypoxia, several treatment studies targeting inflammation suggest that this process may precede the development of the disorder. A recent cross-sectional study in the Penn State Child Cohort (PSCC) revealed that inflammation largely mediates the association between visceral adiposity and OSA in adolescence. The purpose of this study was to examine for the first time whether, long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 54 publications
2
15
1
4
Order By: Relevance
“…Interestingly, all of these biomarkers except fibrinogen were correlated with sleep time spent with SaO 2 less than 90% (TST90), and fibrinogen was related to active smoking [ 34 ]. Similar studies conducted by other researchers demonstrated parallel results; CRP was positively correlated with AHI, even adjusted for BMI [ 39 42 ].…”
Section: Inflammation In Osassupporting
confidence: 84%
“…Interestingly, all of these biomarkers except fibrinogen were correlated with sleep time spent with SaO 2 less than 90% (TST90), and fibrinogen was related to active smoking [ 34 ]. Similar studies conducted by other researchers demonstrated parallel results; CRP was positively correlated with AHI, even adjusted for BMI [ 39 42 ].…”
Section: Inflammation In Osassupporting
confidence: 84%
“…Visceral fat accounts for 5–8% of total body fat in women and increases during menopause, and up to 10–20% in men [23], which may, in large part, explain the sex dimorphism in OSA prevalence. Of note, longitudinal pediatric studies have also demonstrated that incident OSA in adolescents is most strongly predicted by childhood waist circumference [24], and OSA severity in adolescence is positively associated with a greater increase in waist circumference between childhood and adolescence [25].…”
Section: Obstructive Sleep Apnea and Metabolic Syndrome: The Chicken mentioning
confidence: 99%
“…Similarly, children with resolved OSA showed increased baroreflex sensitivity and children with resolved or unresolved OSA demonstrated decreased blood pressure variability after four years [50]. Increased hsCRP, denoting increased inflammation, in childhood was related to later worsened OSA in adolescence in another study [21]. A full prospective evaluation of potential cardiometabolic biomarkers and adiposity with snoring is completed for the first time herein.…”
Section: Discussionmentioning
confidence: 99%
“…A few prospective studies have looked at only inflammation and overweight/obesity in association with snoring and OSA, but not in-depth the complete spectrum of cardiometabolic biomarkers [20,21]. For instance, OSA in obese children was associated with greater visceral fat area derived using MRI [22].…”
Section: Introductionmentioning
confidence: 99%